Unmasking herd protection by an oral cholera vaccine in a cluster-randomized trial. (9th April 2019) - Ali, Mohammad; Qadri, Firdausi; Kim, Deok Ryun; Islam, Taufiqul; Im, Justin; Ahmmed, Faisal; Chon, Yun; Islam Khan, Ashraful; Zaman, Khalequ; Marks, Florian; Clemens, John D
Abstract: Background: Several studies have shown that inactivated, whole-cell oral cholera vaccines (OCVs) confer both direct protection on vaccinees and herd protection on populations. Because our earlier cluster-randomized effectiveness trial (CRT) in urban Bangladesh failed to detect OCV herd protection, we reanalysed the trial to assess whether herd effects were masked in our original analysis. Methods: A total of 267 270 persons were randomized to 90 approximately equal-sized clusters. In 60 clusters persons aged 1 year and older were eligible to receive OCV and in 30 clusters persons received no intervention and served as controls. We analysed OCV protection against severely dehydrating cholera for the entire clusters, as in our original analysis, and for subclusters consisting of residents of innermost households. We hypothesized that if OCV herd protection was attenuated by cholera transmission into the clusters from the outside in this densely populated setting, herd protection would be most evident in the innermost households. Results: During 2 years of follow-up of all residents of the clusters, total protection (protection of OCV recipients relative to control residents) was 58% [95% confidence interval (CI): 43%, 70%; P <0.0001], indirect protection (protection of non-OCV recipients in OCV clusters relative to control participants) was 16% (95% CI: –20%, 41%; P =0.35) and overall OCV protection (protection of all residents in the OCV clusters relative to control residents) was 46% (95% CI: 30%, 59%; P <0.0001). Analyses of the inner 75% and 50% households of the clusters showed similar findings. However, total protection was 75% (95% CI: 50%, 87%, P <0.0001), indirect protection 52% (95% CI: –9%, 79%; P =0.08) and overall protection 72% (95% CI: 49%, 84%; P <0.0001) for the innermost 25% households. Conclusion: Consistent with past studies, substantial OCV herd protective effects were identified, but were unmasked only by analysing innermost households of the clusters. Caution is needed in defining clusters for analysis of vaccine herd effects in CRTs of vaccines.